A New Diagnostic Algorithm for Examining Patients with Suspected Chronic Coronary Syndrome: Questions Remain? - A. N. Sumin (Столичная издательская компания, 2020)
In the new recommendations of the European Society of Cardiology for Chronic Coronary Syndrome, a new diagnostic algorithm is proposed in patients with suspected coronary artery disease (CAD). The purpose of this algorithm was to propose a solution of the accumulated problems in the diagnosis of CAD, in particular, a high frequency of negative non-invasive tests and unchanged coronary arteries during invasive coronary angiography. The new diagnostic algorithm includes a revision of the pre-test probability scale, the introduction of the concept of clinical probability, clarifies the role of various non-invasive tests with the central role of non-invasive testing for myocardial ischemia. However, due to the lack of data on a number of key issues, significant gaps remain that impede the use of this algorithm in practice. This review is devoted to the consideration of problematic issues of the proposed algorithm, while a critical analysis of the algorithm itself and an assessment of recent publications are carried out. Various aspects of the application of a new scale for assessing pre-test probability, determining the clinical probability of CAD, the choice of non-invasive and invasive diagnostic tests, the place of the load electrocardiography test in the diagnosis of coronary heart disease are examined in detail. Gaps in the evidence base and limitations of the algorithm are considered, as well as the possibility of its use in Russian conditions. This review can help in adapting new recommendations to domestic conditions, as well as help practitioners to use it in their daily work.